Hot Deformation Behavior and Workability Characteristic of SiCp/Al-Cu-Mg-Ag Composite - Ning Li; Zhenlin Zhang; Ying Xiao; Kecai Liu; Jin Nie; Fengliang Tan (Materials Research)
The hot deformation behaviors of the 20wt% SiCp/Al-Cu-Mg-Ag composite were studied by establishing processing map and characterizing the microstructure evolution. The hot deformation behavior of the SiCp/Al-Cu-Mg-Ag composite was analyzed through stress-strain curves, and a constitutive equation for its hot deformation was established. Based on the dynamic material model, a processing map for the composite was constructed. The results indicate that the true stress decreases rapidly with increasing temperature and tends to stabilize or slightly decrease after reaching its peak. Furthermore, the peak stress increases with decreasing deformation temperature or increasing strain rate. The flow stress behavior of the SiCp/Al-Cu-Mg-Ag composites can be described by a hyperbolic Arrhenius equation, with a heat activation energy (Q) of 222.3 kJ/mol. The SiCp/Al-Cu-Mg-Ag composite can be deformed stably in the high-temperature, low-strain-rate region. The optimal deformation conditions are identified as 475-500°C and 0.01-0.1s-1, with a maximum dissipation efficiency of 34%.